2021
DOI: 10.1101/2021.03.05.434018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysbiotic oral and gut viromes in untreated and treated rheumatoid arthritis patients

Abstract: Background: Rheumatoid arthritis (RA) has been considered to be influenced by bacteria from the oral cavity and gut for many years. Despite potential impact of viruses in RA was mentioned in some studies, specific roles of oral and gut viromes in RA is still unclear. Results: In this study, we observedthe viral community variation in the oral and gut samples, performeda comparative analysis of oral and gut viromes in health controls, untreated and treated RA patients,and constructed interaction networks among … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Some ubiquitous viruses such as the Epstein-Barr virus (EBV) that infect in the oral cavity can probably contribute to oral cancers ( Guidry et al., 2018 ), and the alterations of the oral viral community have been linked to a wide range of oral diseases such as periodontal disease ( Ly et al., 2014 ), lichen planus ( Carrozzo, 2008 ), and hand, foot, and mouth disease ( Ho et al., 2021 ). Also, our previous study had shown that the diversity and structure of saliva and dental plaque viromes were distinctly changed in patients with rheumatoid arthritis and were correlated with their therapeutic plans ( Guo et al., 2021b ). In addition, longitudinal analysis had revealed that the oral virome of healthy subjects was highly diverse, individually specific, and temporally stable ( Abeles et al., 2014 ; Pride et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some ubiquitous viruses such as the Epstein-Barr virus (EBV) that infect in the oral cavity can probably contribute to oral cancers ( Guidry et al., 2018 ), and the alterations of the oral viral community have been linked to a wide range of oral diseases such as periodontal disease ( Ly et al., 2014 ), lichen planus ( Carrozzo, 2008 ), and hand, foot, and mouth disease ( Ho et al., 2021 ). Also, our previous study had shown that the diversity and structure of saliva and dental plaque viromes were distinctly changed in patients with rheumatoid arthritis and were correlated with their therapeutic plans ( Guo et al., 2021b ). In addition, longitudinal analysis had revealed that the oral virome of healthy subjects was highly diverse, individually specific, and temporally stable ( Abeles et al., 2014 ; Pride et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are crucial members of the microbial ecosystem in the human gut and are often underemphasized in early studies. In recent years, many studies have determined that several human systemic diseases, such as rheumatoid arthritis and inflammatory bowel disease (8)(9)(10)(11), were associated with both gut bacteria and viruses. Although some studies pointed out the association between specific viruses and CRC (12)(13)(14)(15), only a few of them involved in the gut virome of CRC so far.…”
Section: Introductionmentioning
confidence: 99%